Relationship between Social Media for Social Marketing in Family Planning - Ardiansyah, Ardiansyah (ASEAN Marketing Journal, 2021)
This research aims to examine the influence of marketing mix carried out media performance social media portal on attitude towards a social marketing program,and its relationship with source credibility of the portal. This study was focused on "Generasi Berencana" Program (Generation with Plan Program, a program aimed at educating the youth on family planning) The Research employed Structural Equations Modeling (SEM). Based on data from 150 respondents it can be concluded that in social marketing programs, source credibility, engagement, word of mouth have positive influence on the formation of behavior, but awareness of a program is not found to influence formation of behavior. This research also obtained findings that attitudes influence behavioral intention, but subjective norms is not positively influence the formation of behavioral intentions.